Predicting Survival in Combined Post- and Pre-capillary Pulmonary Hypertension associated with Heart Failure and Preserved Ejection Fraction - Arunachalam, Ambalavanan. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Jessica Paulus.; Committee: Nicholas Hill, Harrison Farber, Ioana Preston, and Jason Nelson.; Keywords: Medicine, and Health sciences.